2003
DOI: 10.1002/jtra.10041
|View full text |Cite
|
Sign up to set email alerts
|

Dietary boron: An overview of the evidence for its role in immune function

Abstract: This review summarizes the evidence for boron essentiality across the biological spectrum with special focus on biochemical pathways and biomolecules relevant to immune function. Boron is an essential trace element for at least some organisms in each of the phylogenetic kingdoms Eubacteria, Stramenopila (brown algae and diatoms), Viridiplantae (green algae and familiar green plants), Fungi, and Animalia. Discovery of several of the currently recognized boron-containing biomolecules was achieved because the bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 60 publications
(52 reference statements)
1
71
0
9
Order By: Relevance
“…Boron (B) is either directly related to immune defense mechanisms or indirectly affects components of the immune system [7]. Dietary boron affects the function of many metabolic enzymes, metabolism of steroid hormones, metabolism and utilization of several micronutrients, including calcium, magnesium, vitamin D [8], copper, nitrogen, triglycerides, glucose, and estrogen.…”
Section: Boronmentioning
confidence: 99%
“…Boron (B) is either directly related to immune defense mechanisms or indirectly affects components of the immune system [7]. Dietary boron affects the function of many metabolic enzymes, metabolism of steroid hormones, metabolism and utilization of several micronutrients, including calcium, magnesium, vitamin D [8], copper, nitrogen, triglycerides, glucose, and estrogen.…”
Section: Boronmentioning
confidence: 99%
“…[37] Although boron-containing natural products are rare, several bioactive compounds containing boron have been identified, including the antibiotic boromycin and several bacterial quorumsensing molecules, suggesting a role for boron in cell signalling and the immune function. [38,39] The potential role of boric acid as a cancer chemopreventing agent has been suggested by epidemiological and laboratory studies and it was recently documented in more detail for prostate cancer. [40] Several synthetic boron-containing molecules were recently shown to exhibit important biological properties prompting their investigation as potential therapeutics.…”
Section: Biological and Medicinal Applicationsmentioning
confidence: 99%
“…Borate can cross-link molecules because it contains two pair of hydroxyl moieties that can form reversible diester bonds with molecules containing cisdiols in a favorable conformation. The importance of borate serving as a cross-linking molecule is highlighted by the discovery of several borate-dependent molecules, including rhamnogalacturonan II (RG-II) in plant cell walls (Ishii and Matsunaga, 1996;Kobayashi et al, 1996;O'Neill et al, 1996;Kaneko et al, 1997;Matoh, 1997), boron-polyhydric alcohol complexes identified from phloem extracts (Hu et al, 1997), a bacterial signaling molecule and its sensor protein (Chen et al, 2002), as well as several antibiotics (Hunt, 2003).Boronates (i.e. boronic acids) are a structurally similar but diverse class of molecules that can form reversible ester bonds with cis-diols in a manner functionally identical to borates (Bergold and Scouten, 1983;Springsteen and Wang, 2002).…”
mentioning
confidence: 99%